2018
DOI: 10.1159/000488146
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Traumatic Spinal Cord Injury in Ireland, 2010–2015

Abstract: Background: The International Spinal Cord Society and World Health Organisation recommend the collection of epidemiological data on traumatic spinal cord injury (TSCI). A 1-year prospective study is ongoing in Ireland. While the results of this study are awaited, it was concluded from a feasibility exercise that a complete retrospective dataset, 2010–2015, could be obtained and would be useful for service planning. Methods: All patients with TSCI discharged from the national SCI acute and rehabilitation centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…This is because assault is a very uncommon cause of TSCI in Ireland, sometimes not occurring at all during a calendar year, in stark contrast to other jurisdictions [8]. Finally, the 3 cases of iatrogenic injury included under the term "other" and accounting for 4.9% of injuries is constant in Ireland [4] but less common than that reported elsewhere [19].…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…This is because assault is a very uncommon cause of TSCI in Ireland, sometimes not occurring at all during a calendar year, in stark contrast to other jurisdictions [8]. Finally, the 3 cases of iatrogenic injury included under the term "other" and accounting for 4.9% of injuries is constant in Ireland [4] but less common than that reported elsewhere [19].…”
Section: Discussionmentioning
confidence: 97%
“…This revealed that the incidence of TSCI ranged from 11.5 to 13.3 per million per year over that study period [4]. Falls were the most common cause of injury and incomplete tetraplegia, the most common sub-group of injury [4]. Mean age at injury onset was lowest in 2010, 44.1 (19.3) years and highest in 2014, 52.6 (20.1) years [4].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations